اقبال کی نظم پر مذاہبِ عالم کے اثرات (Al-Qamar, 2023)
Allama Iqbal is always praised for his superior quality poetry of religious zeal. His poetry is based on a certain level religious insight which must be understood and realized by average Muslims to better evolve into a United Nation. His poetic work is revolutionary in spirit and can be read as a complaints about the lethargy of Muslims and the decadence of their civilization. His poetry is amalgamation of religious beliefs, traits and ideologies and ethical values of almost all prominent religion of this universe. His poetry is based on the concept of humanity and forbearance essential for the welfare of mankind. He was blessed with matchless innovative poetic approach and wrote several poems depicting properties of various religions. Not only Islam, Buddhism, Sikhism, Hinduism, Christianity and Jewish had importance near him. In his poem "Nanak" he talked about Guru Nanak and monotheism. Iqbal also employed the Sanskrit phrase "Mantra, shakti in his poems. As for as Buddhism is concerned, he pointed out that "salvation lies in exchanging desire". Consequently, his poetic work portrays basic concepts of Christianity and Jewism religion
Keywords: Allama Iqbal; poetry; religions; humanity; Christianity; Jewish; Buddhism; Decadence; lethargy; monotheism; Bear; Nanak; Mantra; Shakti